A Photographic Journey through the Cretaceous-Tertiary Stratigraphy of the Meratus Mountains-Barito Basin Margin, SE Kalimantan - J.T. (Han) van Gorsel (Ikatan Ahli Geologi Indonesia, 2016)
The SE margin of the Barito Basin shows a relatively simple succession of WNW dipping beds, brought to the surface during Late Miocene or younger uplift of the Meratus Mountain Range. Outcrops of Cretaceous - Miocene rocks can be studied east of the Trans-Kalimantan Highway East and NE of Banjarmasin, between Martapura in the south and Rantau and Kandangan in the north.A vast body of literature exists on the geology of this region. For references see the 'Bibliography of the geology of Indonesia and surrounding areas' (online at www.vangorselslist.com)The photos shown here were taken by the author in 2010, during a fieldtrip reconnaissance along the uplifted eastern margin of the Barito Basin along the SW Meratus Range. I’d like to thank Afin Sjapawi and Ellen de Man (ExxonMobil) and Agus Pujubroto and Roy Widiarta (Sugico) and others for guidance and help with logistics.